Economic Insecurity in Australia: Who is Feeling the Pinch and How?1. Issue 292 (26th October 2014) - Rohde, Nicholas; Tang, Kam Ki; Osberg, Lars; Rao, D.S. Prasada
Abstract : We produce micro‐level estimates of economic insecurity in Australia using a range of different approaches. Measures are calculated annually from 2001 to 2011 and it is observed that when aggregated, they loosely track the national unemployment rate and GDP growth rate. The insecurity indices are then stratified using a number of demographic variables and it is observed that young, unmarried persons with low educational attainments are more insecure than the general population. Panel data regressions show that these individuals are also more insecure when controlling for various factors including time‐invariant individual‐specific heterogeneity. Further, dynamic models indicate that most individuals have high persistence in insecurity over time.